EFEKTIVITAS WAYANG HIP HOP SEBAGAI MEDIA KRITIK SOSIAL (Studi Pada Grup Wayang Hip Hop Di Studio Wayang Hip Hop, Kadipiro, Ngestiharjo, Kasihan Bantul, Yogyakarta) - Suryaningrum, Yulia (Transformasi, 2015)
Wayang hip hop is one of a grup of social media for public critism. The study ims determinethe effectiveness of the delivery of message wayang hip hop community, is effective to changethe attitudes and behavior of society. In the proces of delivering a message communicationeffectiveness, not only influenced by the communication, but also factors communicant.Delivery of message by a wayang hip hop is so that people can understand, comprehend, tochange behavior. Efectiveness wayang hip hop in the delivery of message to the level ofcognitive and affective level.Key Words: Effectiveness of the message, Wayang hip hop, Social criticism.